Confiscated Assets and School: From the Narration to the Experiences of Pathways for Soft Skills and Orientation - Patrizia Belfiore; Antonio Esposito; Domenico Tafuri (University of Bologna, 2023)
Today, after the family, the school is the first institution in which children experience the implementation of social rules and the behaviors that follow from them. It is useful, therefore, to insert paths that favor the consolidation of a system made up of rules, inspired by the principles of transparency, fairness and solidarity, which can be the first and most effective lesson of democratic legality. In this perspective, teaching activities can appropriately refer to the programmatic contents of the disciplines which, not only with regard specifically to civic education and law, but also with regard to other cultural areas, are bearers of explicit information and formative experiences. Particular attention is paid today to the planning of "Percorsi per le Competenze Trasversali e l'Orientamento" [Paths for Soft Skills and Guidance] (PCTO), which will also have an implicit educational value, that consisting in showing, through field experiences, the convergence of multiple cultural interests towards the purpose of education to legality.